Partisipasi belajar IPS melalui quick on the draw learning model pada peserta didik kelas IV sekolah dasar - Novia Hikma Wardani; Sukarno Sukarno; Chumdari Chumdari (Universitas Sebelas Maret, 2020)
This research was a classroom action research (CAR) which purposed to increase the participation learning skills throughout used Quick on the Draw Learning Model. The subjects were the teacher and 24 students from 4th grade of state primary school at Surakarta on the 2019/2020 academy year. This classroom action research consisted of two cycles which each of those cycles had two meetings. The data collection technique in this research used interview, observation, questionnaires, and documentation. The validity of data used construct validation, data source triangulation and technique triangulation. This research used an interactive analysis model of Miles-Huberman. The result of the research shows the increased participation learning skills from 20,83% to 41,67% in the first cycle, and 83,33% in the second cycle. The result of average indicator data from the questionnaire increase from 60,74% to 72,91% in the first cycle and increased again to 83,66% in the second cycle. Based on the result of this research, it was concluded that participation learning skills in social science lessons increased after the Quick on the Draw Learning model was implemented.